Updates on COVID-19: Virology, Etiology, Epidemiology, Pathogenesis, Diagnosis, Transmission and Prevention (Bangladesh Pharmaceutical Journal, 2022)
COVID-19 is a pandemic malady caused by SARS-CoV-2, a novel coronavirus. It is a global threat that has affected 223 countries and territories all over the world. According to the WHO report as of April 06, 2022 coronavirus has affected 492,189,439 people globally with 6,159,474 confirmed deaths. The pandemic of COVID-19 has badly affected Bangladesh likewise many other countries of the world. According to Worldometer report on 06 April 2022 the number of confirmed cases of COVID-19 were 1,951,903 with 29,123 deaths, and 1,886,036 COVID-19 recoveries in Bangladesh. After originating from China, this notorious virus has been spread to almost all the countries of the world. Its spike protein aids in binding with the ACE2 receptors of the cell membrane resulting in cell entry, replication, and induction of inflammatory and pro-inflammatory responses leading to the pathogenic condition. The novel COVID-19 virus has structural and genetic similarity with its predecessors specially SARS-CoV and MERS-CoV. This review presents the existing literature on COVID-19 and discusses different aspects of COVID-19 including virology, etiology, epidemiology, pathogenesis, diagnosis, transmission and susceptibility and preventive measures of COVID-19.Bangladesh Pharmaceutical Journal 25(2): 143-163, 2022 (July)